Blood-Based Liquid Biopsy for Comprehensive Cancer Genomic Profiling Using Next-Generation Sequencing: An Emerging Paradigm for Non-invasive Cancer Detection and Management in Dogs - Kruglyak, Kristina M.; Chibuk, Jason; McLennan, Lisa; Nakashe, Prachi; Hernandez, Gilberto E.; Motalli-Pepio, Rita; Fath, Donna M.; Tynan, John A.; Holtvoigt, Lauren E.; Chorny, Ilya; Grosu, Daniel S.; Tsui, Dana W.Y.; et al. (Frontiers in Veterinary Science, 2021)
This proof-of-concept study demonstrates that blood-based liquid biopsy using next generation sequencing of cell-free DNA can non-invasively detect multiple classes of genomic alterations in dogs with cancer, including alterations that originate from spatially separated tumor sites. Eleven dogs with a variety of confirmed cancer diagnoses (including localized and disseminated disease) who were scheduled for surgical resection, and five presumably cancer-free dogs, were enrolled. Blood was collected from each subject, and multiple spatially separated tumor tissue samples were collected during surgery from 9 of the cancer subjects. All samples were analyzed using an advanced prototype of a novel liquid biopsy test designed to non-invasively interrogate multiple classes of genomic alterations for the detection, characterization, and management of cancer in dogs. In five of the nine cancer patients with matched tumor and plasma samples, pre-surgical liquid biopsy testing identified genomic alterations, including single nucleotide variants and copy number variants, that matched alterations independently detected in corresponding tumor tissue samples. Importantly, the pre-surgical liquid biopsy test detected alterations observed in spatially separated tissue samples from the same subject, demonstrating the potential of blood-based testing for comprehensive genomic profiling of heterogeneous tumors. Among the three patients with post-surgical blood samples, genomic alterations remained detectable in one patient with incomplete tumor resection, suggesting utility for non-invasive detection of minimal residual disease following curative-intent treatment. Liquid biopsy allows for non-invasive profiling of cancer-associated genomic alterations with a simple blood draw and has potential to overcome the limitations of tissue-based testing posed by tissue-level genomic heterogeneity.